Eco-friendly HPLC method by using response surface design to measure a combination of three antidiabetic drugs - Al-Tannak Naser F.; Hemdan Ahmed (Reviews in Analytical Chemistry, 2023)
In recent years, there has been a significant increase in the application of green chemistry principles in analytical chemistry. One of the key factors affecting the environmental sustainability of analytical methods is the choice of solvent. In this particular study, a two-factor, three-level response surface design was employed to develop an environmentally friendly chromatographic technique for a mixture of metformin, glimepiride, and pioglitazone. Ethanol, which is known to be harmless to the environment, was chosen as the organic modifier in the mobile phase. The separation of the mixture was achieved using a phosphate buffer solution (pH 3) mixed with ethanol (30:70 v/v). The linearity of the developed method covered a concentration of metformin of 10–120 µg·mL−1 with a correlation coefficient of 0.9998, glimepiride of 0.1–20 µg·mL−1 with a correlation coefficient of 0.9997, and pioglitazone of 1–50 µg·mL−1 with a correlation coefficient of 0.9999. To evaluate the environmental friendliness of the developed method, two assessment tools were employed: The Analytical GREEnness metric and Green Analytical Procedure Index. The results revealed that the developed method performed exceptionally well in terms of its eco-friendliness. Furthermore, the developed method was compared to other reported methods in terms of both accuracy and environmental sustainability. The results demonstrated that the developed method serves as an excellent alternative to well-established techniques for the separation and quantification of the analyzed mixture. Overall, this study highlights the importance of integrating green chemistry principles into analytical chemistry practices.